1979
DOI: 10.1042/cs0560299
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Level and Renal Clearance of Oxalate in Normal Subjects and in Patients with Primary Hyperoxaluria or Chronic Renal Failure or Both

Abstract: 1. Plasma oxalate has been measured by a radioisotopic method applicable to all concentrations of plasma oxalate and renal function, and also by an enzymatic method which was only applicable to raised concentrations of plasma oxalate. 2. Where the two methods could be applied simultaneously, the agreement between them was good. 3. Plasma oxalate was 86% ultrafiltrable at concentrations of up to 44 micromol/l. 4. Oxalate clearance and the exchangeable oxalate pool were also measured. The ratio of oxalate cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(18 citation statements)
references
References 4 publications
1
16
1
Order By: Relevance
“…Serum oxalate concentration increases during chronic renal failure (1,2), and is above normal in virtually all patients who require chronic dialysis (3)(4)(5), because oxalate is removed from the body almost entirely by filtration at the renal glomerulus (6)(7)(8) and by secretion in the early portions of the proximal tubules (9-1 1). In some patients with chronic renal failure, crystals of calcium oxalate have been identified in kidney, blood vessels, myocardium, thyroid, synovia, cartilage, bone, and periodontium (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Serum oxalate concentration increases during chronic renal failure (1,2), and is above normal in virtually all patients who require chronic dialysis (3)(4)(5), because oxalate is removed from the body almost entirely by filtration at the renal glomerulus (6)(7)(8) and by secretion in the early portions of the proximal tubules (9-1 1). In some patients with chronic renal failure, crystals of calcium oxalate have been identified in kidney, blood vessels, myocardium, thyroid, synovia, cartilage, bone, and periodontium (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, increased plasma oxalate levels have proven to be of value. Whilst raised plasma oxalate levels were documented in case 1 on two occasions neither value exceeded levels associated with the degree of renal failure [9], Oxalate deposits in the bone marrow aspirate has been an infrequent finding in PH [1,2], as was the case in our patients. In these cir cumstances, bone wedge biopsy or transcutaneous bone biopsy is the procedure of choice, being more represen tative than aspirate to confirm the diagnosis [14].…”
Section: Discussionmentioning
confidence: 73%
“…A presumptive diagnosis of PH was made on histological findings and the cardiological manifestation of com plete heart block [8]. However, two subsequent pre-dialysis samples taken 3 months apart revealed plasma oxalate levels of 3.0 pg/ml (33 pmol/l) [serum creatinine 7.9 mg/dl (700 pmol/l)] and 3.64 pg/ ml (40 pmol/l), [serum creatinine 1 1.8 mg/dl (1,045 pmol/l)]; oxalate/creatinine ratios: 0.047 and 0.038 subsequently; these levels are normal for the degree of renal failure [9] and were therefore consid ered to be inconsistent with PH. The patient received a cadaveric transplant in February 1986. and immunosuppression with ciclosporin and prednisolone.…”
Section: Casementioning
confidence: 99%
“…The results of serum oxalate determinations in normal subjects reported by Borland et al [1] in their recent paper (0-55 um ol/l) are far out of the range found in normal subjects as determined by in vivo isotope clearance meth ods (below 3 pm ol/l) [2], The reason why in many earlier studies in which chemical methods were used concentra tions are reported exceeding these low values by one order of magnitude is not clear [3), but in more recent studies [2,3,[6][7][8][9][10][11][12][13] normal values much closer to the true value were found, i.e. at least lower than 6 pm ol/l (table 1).…”
mentioning
confidence: 79%